Co-delivery of anti-inflammatory and antioxidant agents via polymersomes for osteoarthritis therapy - Rui, Mengjie; Wang, Li; Mi, Ke; Li, Yinfeng; Fang, Naying; Ge, Yingying; Feng, Qiuqi; Luo, Yaqi; Feng, Chunlai (Frontiers in Pharmacology, 2025)
BackgroundOsteoarthritis (OA) is a chronic degenerative joint disease primarily driven by inflammation and oxidative stress. This study aimed to develop a polymersome-based co-delivery system encapsulating hydrophilic cordycepin and hydrophobic phenylboronic acid (PBA) to enhance their solubility, stability, and therapeutic efficacy against OA.MethodsFormulation parameters were optimized using a Taguchi orthogonal design to achieve high encapsulation efficiency, sustained drug release, and effective reactive oxygen species (ROS) scavenging. In vitro anti-inflammatory effects were evaluated in LPS-activated RAW 264.7 macrophages by assessing TNF-α, IL-1β, and extracellular ROS levels. Therapeutic efficacy was further validated in a papain-induced OA rat model treated with co-loaded polymersomes via intraperitoneal injection for four weeks, with joint swelling and serum cytokines monitored.ResultsThe optimized co-loaded polymersomes exhibited an average size of 101.03 ± 0.42 nm and a polydispersity index (PDI) of 0.248 ± 0.014. They demonstrated a H2O2-responsive compound release and potent ROS-scavenging ability. In vitro, the co-loaded polymersomes significantly reduced inflammatory cytokines and ROS levels. In OA rat model, co-loaded polymersomes led to the greatest reduction in cartilage damage and promoted cartilage regeneration compared to other treatment groups.ConclusionThis co-delivery system offered a sustained release profile, enhanced joint targeting, and reduced adverse effects, resulting in superior therapeutic outcomes compared to free compounds alone or their combination. These findings highlighted its potential as a promising therapeutic approach for OA management.